The impact of life enrichment programs to improve quality of life on self-esteem and psychological capital of female-headed households - Zareh, Fatemeh; Manshaee, Gholamreza; Keshtiaray, Narges (Applied Family Therapy Journal (AFTJ), 2021)
Aim: This study aimed to determine the impact of life enrichment programs to improve the quality of life on self-esteem and psychological capital of female-headed households.Methods: This study was quasi-experimental with a pretest-posttest design with a control group and a two-month follow-up. The statistical population of the present study consisted of 130 female-headed households (deceased or divorced spouses) under the auspices of Imam Khomeini Relief Committee of Marvdasht city in 2009-2010. After screening the population by Crocker et al.'s (2003) Self-Esteem Questionnaire and psychological capital of Lutans and Olio (2007), 30 female-headed households were selected by convenience sampling method and randomly assigned to experimental and control groups (15 women in each group). The experimental group received the intervention of life enrichment programs to improve quality of life (researcher-made) in sixteen 90-minute sessions over two months. The data were analyzed by repeated-measures analysis of variance using SPSS23 statistical software. Results: The results indicated the impact of quality of the intervention of life enrichment programs to improve quality of life on self-esteem score (F = 14.71, P = 0.002) and psychological capital (F = 20.90, P = 0.001). Also, the results were stable in the follow-up phase. Conclusions: According to the findings of the present study, it can be concluded that by using the techniques of responsibility, self-awareness, patience, acceptance, and mindfulness, life enrichment programs to improve quality of life can be used as an effective method to improve the self-esteem and psychological capital of female-headed households.